Improvement of Electrical Properties of CMC-PVA Doped with Various Contents of LiNO3 as an Application for Hybrid Polymer Electrolytes - Zulkifli, Amalia; Mazuki, Norfatihah; Samsudin, Ahmad Salihin (UI Scholars Hub, 2021)
The present work was carried out with the development of hybrid polymer electrolytes (HPEs) by using carboxymethyl cellulose (CMC)–polyvinyl alcohol (PVA) doped with different contents of lithium nitrate (LiNO3) for the determination of their structural and conduction properties. The structural analysis was conducted by using Fourier transform infra-red spectroscopy and showed the interaction between the blend host polymer and ionic dopant, which formed via the coordinating site of CMC-PVA and Li+-NO3−. The complexes of CMC-PVA doped LiNO3 led to an increment in ionic conductivity, as observed by electrical impedance spectroscopy, and the sample containing 20 wt% LiNO3 obtained the highest ionic conductivity of 3.54 × 10−3 S cm−1 at room temperature. The ionic conductivity at different temperatures (from 303 K to 343 K) was measured and found to obey the Arrhenius rule. The activation energies of the HPEs were computed based on the Arrhenius equation and were inversely proportional to the ionic conductivity. The highest ionic conducting sample was fabricated into an electrical double layer capacitor (EDLC). Cyclic voltammetry (CV) was used to study the electrochemical performance of the EDLC. A high value of Cs was obtained at 2 mVs−1 due to the utilization of ions in the vacant sites of the electrode material.